And nothing but the truth - Sekulow, Jay.; Fournier, Keith A., 1954- (Nashville : T. Nelson Publishers, 1996)
In the 1960s a shadow of religious persecution fell across America. Public schools became as hostile to religion as their counterparts in Communist countries. Christians were stunned and dismayed. And this persecution increased for decades after that -- and continues even today. The government threatens intervention if workers display Bibles on their desks or mention their faith to coworkers. Local zoning committees deny churches protection against zoning laws that allow bars in their vicinity. Local governments ban films by Christians like James Dobson in public facilities. In And Nothing But the Truth you will learn how you can be a part of the new revolution of religious freedom sweeping our country. And you will discover what you can do to reclaim your community and your own rights.
Part one : a time for new beginnings -- Taking the high ground -- New beginnings -- America's culture of disbelief -- How come you're the target? -- Part two : the battle zone -- Restoring the Christian voice -- Censorship on campus -- To pray or not to pray -- The abortion distortion -- When death walks the street -- Don't let the smoke get in your eyes -- The gospel on main street -- Part three : the future -- The road to tomorrow.
"A Janet Thoma book."
Includes bibliographical references (p. 259-266) and index.
Keywords: Freedom of religion -- United States -- History -- 20th century; American Center for Law and Justice; Church and state -- United States -- History -- 20th century; United States -- Church history -- 20th century; United States -- Politics and government -- 1993-2001.